The British Monarchy On Screen - Merck, Mandy (Manchester University Press, 2016)
Moving images of the British monarchy, in fact and fiction, are almost as old as the moving image itself, dating back to an 1895 American drama, The Execution of Mary Queen of Scots. British monarchs even appeared in the new 'animated photography' from 1896, led by Queen Victoria. Half a century later, the 1953 coronation of Elizabeth II was a milestone in the adoption of television, watched by 20 million Britons and 100 million North Americans. At the century's end, Princess Diana's funeral was viewed by 2.5 billion worldwide. In the first book-length examination of film and television representations of this enduring institution, distinguished scholars of media and political history analyse the screen representations of royalty from Henry VIII to 'William and Kate'.